Penerapan Sistem Informasi Pemasaran dalam Mendukung Strategi Pemasaran Digital pada Platform E-Commerce Shopee - Fajral Rizka Ramadhan; Khaila Syahira Saldri; Muhammad Ilham (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2026)
The rapid growth of e-commerce in Indonesia has encouraged businesses to adopt digital marketing strategies supported by effective information management. Marketplace platforms such as Shopee provide extensive marketing data with strategic value; however, its utilization requires a structured system. This study aims to analyze the implementation of Marketing Information Systems in supporting digital marketing strategies on the Shopee e-commerce platform. The research employs a qualitative descriptive approach through literature review and indirect observation using internet-based scholarly sources. Data were collected from relevant national and international journals and analyzed descriptively to identify the roles, components, and influencing factors of Marketing Information Systems. The results indicate that Marketing Information Systems play a significant role in supporting digital marketing decision-making through the management of internal records, marketing intelligence, marketing research, and decision support systems. Furthermore, the implementation of Marketing Information Systems on Shopee is influenced by information technology development, company size and scale, consumer behavior, competitive environment, and corporate strategy and objectives. This study is expected to contribute theoretically to the development of digital marketing studies and provide practical references for e-commerce businesses in optimizing data-driven marketing strategies.